Pengaruh green product, green price, green promotion dan social influence terhadap green purchase intention pada produk ramah lingkungan (studi pada produk minyak zaitun brand kecantikan Mustika Ratu) - Muchammad Ali Muchsin Al Abid (Jurnal Ilmu Manajemen, 2025)
This study is motivated by the declining sales of environmentally friendly products from the beauty brand Mustika Ratu, despite the growing trend in the use of natural and eco-friendly products. The decline is suspected to be influenced by internal factors such as the performance of green product, green price, and green promotion, as well as an external factor, namely social influence. The purpose of this study is to examine the effect of green product, green price, green promotion, and social influence on green purchase intention for Mustika Ratu's Olive Oil product. This research adopts a conclusive descriptive approach with a sample of 220 respondents, consisting of personal care product users aged 18–40 years who are interested in environmentally friendly products. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that: (1) green product has a positive and significant effect on green purchase intention of Mustika Ratu's Olive Oil, (2) green price positively and significantly influences green purchase intention, (3) green promotion also shows a positive and significant effect, and (4) social influence has a positive and significant impact on green purchase intention for the product.